The Remarkable Unresponsiveness of College Students to Nudging and What We Can Learn from It - Philip Oreopoulos; Uros Petronijevic (Institute of Labor Economics (IZA), 2019)
We present results from a five-year effort to design promising online and text-message interventions to improve college achievement through several distinct channels. From a sample of nearly 25,000 students across three different campuses, we find some improvement from coaching-based interventions on mental health and study time, but none of the interventions we evaluate significantly influences academic outcomes (even for those students more at risk of dropping out). We interpret the results with our survey data and a model of student effort. Students study about five to eight hours fewer each week than they plan to, though our interventions do not alter this tendency. The coaching interventions make some students realize that more effort is needed to attain good grades but, rather than working harder, they settle by adjusting grade expectations downwards. Our study time impacts are not large enough for translating into significant academic benefits. More comprehensive but expensive programs appear more promising for helping college students outside the classroom.
Keywords: I2; J24; 330; behavioural economics of education; nudge; college student achievement; coaching; mindset; RCT